2017
DOI: 10.22377/ajp.v11i01.1114
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Main of agriculturists in Singburi was cultivated rice and major pesticides' use is chlorpyrifos; however, farmers are applied bio-extracts to eliminate pest and trend to be organic farming. Hence, organic farmers may become lower risks from pesticides rather than non-organic farmers. Aim: To determine biochemical and hematological status between organic and non-organic farmers, Bang Rachan district, Singburi, Thailand. Materials and Methods: Farmers were separated into organic farmer group (N = 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
2
0
0
Order By: Relevance
“…The present study revealed that SOD was significantly lower among exposed group compared to non-exposed group, (p-value = 0.000) (table 1), this is in agreement with Vidyasagar et al who reported that RBC SOD was lower among exposed versus control group [25]. Other studies in India and Egypt showed the same reduction in the SOD activity in the exposed groups [19][20][21][22][23][24][25][26]. In contrast to these results, some studies found an elevation of SOD levels in exposed group like Simoniello et al [30].…”
Section: Subjects and Methods Study Design And Settingssupporting
confidence: 92%
See 1 more Smart Citation
“…The present study revealed that SOD was significantly lower among exposed group compared to non-exposed group, (p-value = 0.000) (table 1), this is in agreement with Vidyasagar et al who reported that RBC SOD was lower among exposed versus control group [25]. Other studies in India and Egypt showed the same reduction in the SOD activity in the exposed groups [19][20][21][22][23][24][25][26]. In contrast to these results, some studies found an elevation of SOD levels in exposed group like Simoniello et al [30].…”
Section: Subjects and Methods Study Design And Settingssupporting
confidence: 92%
“…Also a lot of studies in Tunisia [17], Nigeria [9], Thiland [18] and India were in accordance with our results [19]. In contrast with this study, studies of Ogut et al [20] and Sudjaroen [21] didn't observe any statistical significant difference between both groups as regard BuChE levels. This contrast may be as a result of different levels of exposure in different countries due to usage of PPE or having washing facilities afire pesticides use.…”
Section: Subjects and Methods Study Design And Settingssupporting
confidence: 90%